Les moyens d'expression du refus en français moderne - Martyniuk, Oksana M.; Мартинюк, Оксана Миколаївна (Національний університет "Острозька академія", 2019)
L’article est consacré à l’étude des moyens d’expression verbaux et non verbaux du refus en français moderne. Les types de refus direct et indirect sont déterminés. Les particularités structurelles et sémantiques des déclarations avec la signification «refus» et leur charge pragmatique sont analysées. Les outils linguistiques explicites et implicites pour exprimer le refus sont caractérisés. Les moyens d’expression du refus, non verbaux (gestes, expressions faciales et même le silence), qui jouent un rôle important dans le processus de communication sont considérés. Dans l’aspect syntaxique, les déclarations avec une valeur du rejet peuvent être exprimées non seulement à l’aide des phrases narratives, mais aussi avec des phrases exclamatives, impératives et des questions rhétoriques. Il est prouvé que le refus doit être convaincant, correct et poli afin de ne pas provoquer une agression. The article is devoted to the study of verbal and non-verbal means of expressing refusal in modern French. Types of direct (using a particle no, a verb in a negative form; statements that indicate impossibility, unwillingness to do something, etc.) and indirect (may appear in the form of justification, deterrence, preference, principle, excuse / regret, avoidance) refusal are determined. Structural and semantic peculiarities of statements with meaning «refusal» and their pragmatic load are analyzed. Explicit and implicit language means of refusal have been characterized. Non-verbal means of refusal (gestures, facial expressions, and even silence), which play a significant role in the process of communication are considered. Knowledge of nonverbal language not only helps to better understand people, but also (and above all) to predict what reaction it caused before speaking, to feel the need for change to achieve the desired result. In the syntactical aspect, statements with a value of refusal can be made not only with narrative sentences, but also with exclamative, imperative sentences and rhetorical questions. It was that the strategy of refusing to execute something may be part of such tactics of communication: – declare incompetent; refer to the inability to respond to the request at this time – refuse without any motivation; to abstain from the answer, to promise nothing concrete; make it clear that you do not wish to complete the application. It is proved that the refusal must be convincing, correct and polite, so as not to cause aggression. Стаття присвячена дослідженню вербальних та невербальних засобів вираження відмови у сучасній французькій мові. Визначено типи прямої та непрямої відмови. Проаналізовано структурні та семантичні особливості висловлювань зі значенням “відмова” та їхнє прагматичне навантаження. Охарактеризовано експліцитні та імпліцитні мовні засоби вираження відмови. Розглянуто невербальні засоби позначення відмови (жести, міміка, і навіть, мовчання), які відіграють значну роль у процесі комунікації. У синтаксичному плані, висловлення зі значенням відмови можуть оформлятися не лише розповідними реченнями, але також окличними, наказовими та риторичними питаннями. Доведено, що відмова повинна бути переконливою, коректною та ввічливою, щоб не викликати агресії
Засоби вираження відмови в сучасній французькій мові
Keywords: refus direct et indirect; moyens d'expression verbaux et non verbaux du refus; refus explicite et implicite; пряма і непряма відмова; вербальні та невербальні засоби вираження відмови; експліцитна та імпліцитна відмова